Effects of castration and weaning conducted concurrently or consecutively on behaviour, blood traits and performance in beef calves. (28th August 2014) - Lambertz, C.; Farke-Röver, A.; Moors, E.; Gauly, M.
<x content-type="archive" xml:space="preserve">Abstract</x> The objectives of this study were to evaluate the effects of Burdizzo castration and abrupt weaning on the behaviour, blood traits and performance of beef calves when weaning was conducted concurrently or consecutively to castration. In total, 64 male beef calves aged between 6 and 7 months were assigned to a 2×2 factorial design with the following treatment groups (n=16 animals per treatment): (1) castrated and concurrently weaned in week 0 (CAS-WEA); (2) castrated in week 0 and weaned in week 4 (CAS-CON); (3) bulls weaned in week 0 (BUL-WEA); and (4) bulls weaned in week 4 (BUL-CON). The behaviour of the calves was observed for 3 days following weaning. Blood was collected weekly from weeks 0 to 5 and analysed for the acute-phase protein haptoglobin, and neutrophil and lymphocyte percentages. BW was recorded weekly from weeks 0 to 7. Animals were slaughtered at 17 months and weight, dressing percentage and carcass classifications were recorded. On day 1 after weaning, the number of vocalizations (calls/10 min) was higher in BUL-WEA (7.2) and CAS-WEA (5.4) than in calves of CAS-CON (2.8) and BUL-CON (2.9) groups (P<0.05). From days 1 to 3 vocalizations decreased in all groups. CAS-CON and BUL-CON animals spent 20% lying on day 1 after weaning compared with 40% in CAS-WEA and BUL-WEA calves (P<0.05). The haptoglobin concentration decreased during the first 5 weeks after weaning in all groups independent of the castration, weaning group or its interaction (P>0.05). WEA groups showed an increased average daily gain (ADG) during weeks 0 to 3 and a reduced ADG during 4 to 7 weeks in comparison with CON animals. At slaughter, bulls were about 80 kg heavier than castrates and had a superior dressing percentage and carcass classification (P>0.05). In conclusion, weaning had a greater effect on the number of vocalizations, standing/walking and lying behaviour and ADG compared with Burdizzo castration. In comparison with undertaking the procedures separately, concurrent castration and weaning neither affected behaviour and haematological parameters nor impaired performance. There was no evidence that the concurrent application of both treatments markedly increased the stress response compared with their application at intervals of a few weeks.